Veszettorvosok Szentesen a XVIII-XIX. században - Mód László (2002)
In the Archives of Szentes there are several written documents with the half of which the presence of madness and the job of its specialists can be traced back to the beginning of the 1910s. From the end of the 18 th century to 1863 the healers precticed their professions as employees of the town. For their job they got annual salary and they had certain privileges. In the barckround of their employment was the fact that until the end of the 19th century there were very few professional veterinary surgeons, therefore the role of unqualified doctors in the life of a community was very important. According to the archival data officially the specialist dealt with the cure of ill animals however at the end of the 19th century they treated people as well. The healers were able to classify the antidotes used in these days. They knew the symptoms of the illnesses and they could separate the infected animals from the health ones. This could be the explanation for their honoured place in society althorities often prohibited their works.
Keywords: Bölcsészettudományok; Történettudomány és régészet